The Theory of Formalism Philosophy in Mathematics Learning - Zafrullah; Atika Miftah Ramadhani; Rizki Tika Ayuni (Penerbit Hellow Pustaka, 2024)
Philosophy has become an important field of study and is now being taught in schools and universities. This development has laid the foundation for the emergence of various schools of thought in modern philosophy. Formalism is an approach in mathematics that emphasizes the importance of using formal rules and mathematical structures in understanding and developing mathematical concepts. This article is a literature study that discusses the development of formalistic philosophy applied in mathematics education.